A survey of music activities in the penal institutions of northeastern United States - Apicella, Anthony (1952)
Thesis (M.A.)--Boston UniversityThe problem. I£ we assume that the function of penal institutions is to reform, which is the modern scientific approach, and that reformation is an educational process -- so music should form an integral part of this phase of education because of its influence and contribution towards the mental health and life development of the individuals in these institutions. This study is an attempt to ascertain the extent to which music activities are carried on in the various types of penal institutions in northeastern United States. It is intended that the present study be regarded as an introductory study in determining the degree to which music activities are being used as part of correctional education. The institutions used in the present study represent the state and federal institutions of northeastern United States which includes those of the states of Maine, New Hampshire, Vermont, Massachusetts, Rhode Island, Connecticut, New York, New Jersey, and Pennsylvania. The penal correctional institutions are of various types including prisons, reformatories, penitentiaries, penal farms, vocational schools, correctional institutions, and institutions for the criminally insane. Since there must be some limitations as to scope in a study of this character, the writer has confined his attention primarily on the following music activities: band, dance orchestra, concert orchestra, choral groups -- religious and non-religious, instrumental instruction, appreciation or listening, minstrel show, and community singing. Another important aspect is determining the extent to which the various institutions have any music activities in which the individuals participate as performers or listeners. Listening would include time spent listening to music over the radio and over the public address systems in the work shops and dining halls. Summary of findings. About one-tenth of the penal institutions that returned the questionnaires have no music activities of any kind, and in about three-tenths only a few music activities are maintained. In the remainder of the penal institutions the music activities are quite varied. The musical activities include listening to music over a reproducing or public address system in the work shop and dining hall, and listening to music over the radio. Other activities are: band, dance, orchestra, concert orchestra, choral groups, instrumental instruction, appreciation or listening, minstrel shows, and community singing. A few of the more progressive institutions put on operettas, and some have advanced classes in music such as -- music theory, harmony, and counterpoint. A number of institutions lack music activities. From the reports made by the various penal directors it is evident that there are several factors influencing this. Among these are insufficient appropriations, lack of space, the need of proper personnel, and the interference of music activities with the work program. From the comments made by the directors or administrators it was made apparent that music activities in the penal institutions of northeastern United States are used and needed by the individuals in these institutions for instruction in wholesome leisure-time activities, for guidance towards the achievement of mental health, and as an aid in a type of social education designed to develop personal insight and an understanding of interpersonal values and community living. [TRUNCATED